Prone spine surgery in a morbidly obese patient: Anesthesia challenges and management - Latkar, Prajakta; Kaushik, Prajwala; Prabhudesai, Aaditya; Mehta, Hemant (Indian Journal of Case Reports, 2022)
India is seeing a rapid epidemiological transition from underweight to overweight, with an overall prevalence of obesity reported to be 40.3%. Anesthesiology concerns in an obese patient are well known. We elaborate on the anesthesia management in a 68-year-old male patient with a body mass index of 66.3 kg/m2 who underwent spine surgery in prone position. Challenges faced ranged from the size of the table to the difficult airway, difficulty in positioning, maintenance of airway and ventilation, maintaining a free abdomen, and anesthesia management with meticulous use of anesthetic drugs for an uneventful recovery.